No Longer a Feuding Society? Legal Practice and Kingship in Late 13th-Century Iceland - Matsumoto, Sayaka, 1982- (2012)
The Icelandic Free State (c.930-1262) is well known as a model of ‘a feuding society,’ due to its unique social system based on the principle of feuding without any jurisdiction by a king. Iceland came under the rule of a Norwegian king in the early 1260s, and it is generally thought that feuds in Iceland came to an end as a result of the royal legislation introduced from 1271. This paper reconsiders this assumption and aims to reveal the legal practice under kingship in late 13th-century Iceland and its relation to the state formation there. Although the information available to us is limited, it does indicate that people kept on feuding long after submitting to the rule of the king. At the same time, the king’s policy was executed by his representatives through institutions such as the summons to Norway or the oath of fidelity, which were based on the new royal law-code. However, the king did not delegate his power to the Icelandic king’s men as much as he did to Norwegian representatives; the Icelandic king’s men also worked for the king, but they did not become the receiver of the oath of fidelity to the king. There was also discrepancy on the matter of the subjects’ obligation between the king and Icelanders: the king, as rex iustus, began to demand absolute obedience from his subjects, but Icelanders were not always aware of it. They maintained their traditional ways of participating in decision making with their ruler, such as feuds or negotiations at assemblies, and the king could not readily prevent them. In the period of the 1270-80s, Iceland was no longer a purely feuding society, and the centralisation of legislative and judicial power in the hands of the king was actually progressed; nevertheless, it should be noted that Icelanders tended to retain their traditional ways, regardless of the demands of the Norwegian king. Keywords: feuds, conflicts, kingship, law, state formation, Iceland, Norway